The economics of financial markets - Bailey, Roy E. (Cambridge University Press, 2005)
"The Economics of Financial Markets presents a concise overview of capital markets, suitable for advanced undergraduates and for beginning graduate students in financial economics. Following a brief overview of financial markets--their microstructure and the randomness of stock market prices--this textbook explores how the economics of uncertainty can be applied to financial decision-making. Emphasis is placed on the economic principles underlying all financial markets, focusing on markets for equities, bonds, futures and options contracts."--Provided by publisher.